BURNOUT SYNDROME IN MEDICAL RESIDENTS - V. Stoyanov (Trakia Journal of Sciences)
Objective: Occupational burnout occurs more often among doctors than among those working in other sectors. It is an indisputable fact that medics whose work requires almost continuous contact with people are more prone to burnout. It is noticed that the burnout syndrome affects doctors at all stages of their careers - from residents to experienced practitioners. Methods:. This paper performs a literature review on the frequency and causes of professional burnout among resident doctors. Results: The results of numerous large-scale studies are conclusive that the intensive workload of doctors, including night shifts and overtime, and the lack of work-life balance, due to the numerous resident duties, are the most common predisposing factors for the development of burnout syndrome in resident doctors. Another important conclusion from these studies is that a high level of BOS is mainly associated with depression and inadequate patient care. Conclusions: Professional burnout syndrome among resident doctors is an ongoing issue. It is then required that additional subjects, such as building skills to recognize and combat stress and implement strategies to overcome it, should be included in resident doctors training programmers.